PTU-027 Is water assisted colonoscopy superior to carbon dioxide assisted standard colonoscopy: results of an observational study. (22nd June 2015) - Kurup, AK; Disney, B; Shetty, S; Ishaq, S
Abstract : Introduction: Water assisted colonoscopy [WAC] is known to reduce patient discomfort and improve the adenoma detection rate [ADR]. 1 In this retrospective observational study, we compared water assisted colonoscopy against standard colonoscopy[SC] using CO2 in a bowel cancer screening positive population. Method: This was a retrospective review of prospectively collected data. The population studied was undergoing colonoscopies following a positive faecal occult blood test as part of the bowel cancer screening programme [BCSP]. Endoscopist A preferred to intubate the caecum using the water exchange method and endoscopist B would insufflate the bowel using carbon dioxide. Sedation and analgesic use was at the discretion of the endoscopist. The primary outcome was the adenoma detection rate and the comfort scores in the two groups. Secondary outcomes included caecal intubation rate, mean withdrawal time, sedation use and polyp retrieval rate. Results: Data from two hundred and seven colonoscopies performed from April 2014 to December 2014 [9 months] were analysed. 102 colonoscopies were performed using the water exchange method [group A] and 105 colonoscopies were performed using CO2 [group B]. Primary outcomes: Adenoma detection rate [ADR] in group A was 53% compared to of 36% in group B. This was statistically significant [difference in rate = -0.1868 [95% CI 0.0052–0.3685 p = 0.0438]. The proportion of patients experiencing none [score 1] or minimal [score2] discomfort [based on modified Gloucester comfort score] were more in group A [n = 74] compared to group B [n = 62]. This was found to be statistically significant [Z = 2.046, p = 0.0408] Secondary outcomes: Conclusion: Our finding of a significant improvement in ADR and better tolerability in the WAC group supports similar conclusions by Hsieh e t al. This may have potential implications for the bowel cancer screening programme since the perception of colonoscopy can influence public participation and improve uptake in the BCSP. Improved ADR may be due to combination of factors like improved bowel preparation, flattening of mucosal folds and floating effect of polyps with water irrigation. We hope our findings are validated in the future through randomised trials. Disclosure of interest: None Declared. Reference: Hsieh YH, Koo M, Leung FW. A patient blinded randomized, controlled trial comparing air insufflation, water immersion and water exchange during minimally sedated colonoscopy. Am J Gastroenterol. 2014;109(9):1390–400